A study to assess the knowledge regarding effects of air pollution on health and its prevention among auto rickshaw drivers of Bagalkot: with a view to develop an information booklet - Shamrao Gaikwad, Abhaykumar (International Journal of Nursing Research, 2023)
Aim: The author wishes to assess the knowledge regarding effects of air pollution and its prevention among the auto rickshaw drivers at Bagalkot city with a view to prepare an information booklet. Material and method: A descriptive study was conducted. Convenient non random sampling method was used to select the sample. The study sample included a sample of 100 auto rickshaw drivers. A structured interview schedule was prepared and used for data collection. Results: The results of the study clearly indicated that out of 100 subjects 53 (53 %) of subjects’ had medium knowledge, 46 (46 %) subjects had inadequate knowledge and only 01 (1 %) had adequate knowledge regarding effects of air pollution on health and its prevention. The total mean percentage was 36.50% with total mean 15.33 and standard deviation 5.30. Conclusion: The significant association was found between level of knowledge and years of experience of study subjects. (χ2 = 6.81, p<0.05) and significant association between level of knowledge and sources of information regarding health. (χ2 = 9.15, p<0.05). Therefore, the research hypothesis H2: There will be significant relationship between knowledge of auto rickshaw drivers regarding effects of air pollution on health and its prevention and their selected socio-demographic variables was accepted.